Direct Multi-Deuterium Labelling of Pirtobrutinib - Kriegelstein, Michal; Hojcsková, Jana; Hroch, Miloš; Marek, Aleš (Journal of labelled compounds & radiopharmaceuticals, 2024)
Herein, we demonstrate an efficient method for multi-deuterium labelling of pirtobrutinib-a Bruton's tyrosine kinase inhibitor recently approved by the FDA-using a straightforward hydrogen isotope exchange (HIE) reaction. A remarkably high level of deuterium incorporation was achieved using an excess of a Kerr-type iridium catalyst. The key factor in the significant deuterium labelling was the decision to employ a deuterium uniformly labelled solvent, chlorobenzene-d5, at an elevated temperature. Virtually, no d0-d3 species were detected, with only traces of d4-d5 isotopomers (< 5%) observable in the mass spectrum of pirtobrutinib-d8, fulfilling requirements for stable isotope-labelled internal standard. The labelled compound-mainly consisting of isotopomers d6-d9 at 82.4% of the total abundance-was isolated in a high yield (73%) and purity (99%). Noteworthy, fluorine group acting as a directing group was observed for the first time. Significant incorporation of deuterium in ortho-positions, exceeding 87%, was observed. Interestingly, chlorinated solvent used in the HIE reactions was non-specifically deuterated yielding up to 0.42 deuterium per chlorobenzene molecule even at an exceptionally low iridium catalyst loading of 4.17 × 10-2 mol%.
Keywords: deuterium; Piperidines; piperidiny; Deuterium; Isotope Labeling; Pyrimidines; pyrimidiny; izotopové značení